Promoting brand loyalty through advertising campaign: qualitative study of nigerian breweries maltina product (2017)
Organizations are forced to anticipate customers' needs and convey clear messages to them through advertising by establishing strong brand names and focusing on brand building. But to what extent can Advertising influence consumers' purchase decision especially in products branding? Hence, the study examined the extent to which advertising campaigns have been used to promote brand loyalty of Maltina product by Nigerian Breweries PLC among its consumers. The study adopts qualitative research methods with the use of in-depth interview and Participant Observation to gather data. Two prominent departments (sales and marketing) were visited while key Managers and Officers were interviewed with close observation to provide insight into the organization's viewpoints to the study. The study revealed that persuasive advertising messages determine consumer's desire for the product(s), with the use of television for the promotion of Maltina as a brand to consumers. This explains the reason why Nigerian Breweries plc. still holds the Maltina family television game show every year. The study also revealed that understanding the needs and wants of the consumers and the venue to which the adverts will be placed to reach the target demographic are the major priorities before designing any advertising message. Other strategies such as celebrities used in the adverts, the family game show (Maltina Dance All), slogans, packaging and television adverts have been effective in increasing purchase for Maltina product. It was also revealed that sales for Maltina product went up with each of these strategies which buttress the fact that product advertising is germane to brand loyalty.